ADVANCED TECHNOLOGY IMPLEMENTATION OF ADAPTIVE DEFENSE SCHEME IN SOUTH AND CENTRAL KALIMANTAN SYSTEM - Brian Ikhsana Putra A W, Ahmad
Kalimantan Interconnection System, consisting of 94 substations and 8,470.45 km of transmission lines, experiences frequent disturbances, primarily in Central Kalimantan. These disturbances, often caused by lightning, highlight the need for improved defense schemes to ensure system reliability. The implementation of the Adaptive Defense Scheme (ADS) for the Kasongan-SLK transmission line aims to address this need by integrating both dynamic and static Over Voltage Transmission Shedding (OVTS) schemes. This paper details the design of ADS hardware specifications to meet the applicable standard. Adaptive Defense Scheme (ADS) demonstrates significant advantages over the existing Special Protection Scheme (SPS). Testing results indicate superior performance of the ADS in data polling, telecommunications, optimization, and GOOSE signal processing, with response times meeting PLN standards. Recommendation for further improvements including redundant telecommunications infrastructure, server and gateway, are also discussed in this paper.